Ecological risk assessment of trace metals in sediments and their effect on benthic organisms from the south coast of Zhejiang province, China. (February 2023) - Zhao, Zhengjia; Liu, Qiang; Liao, Yibo; Yu, Peisong; Tang, Yanbin; Liu, Qinghe; Shi, Xiaolai; Shou, Lu; Zeng, Jiangning; Chen, Quanzhen; Chen, Jianfang
Abstract: To explore the ecological risks of trace metals in sediments and their relationship with benthic organisms, 12 trace metals were analyzed and the macrobenthos were identified in the sediments collected from the south coast of Zhejiang province which belongs to the East China Sea. Spatially, the concentrations of most trace metals were high in the estuary, except for Ba and Sr. There was no obvious enrichment for trace metals, except that the concentration of Cd slightly exceeded the coastal background. The ecological risks calculated by the concentrations of Cr, Cd, Cu, Zn, Pb, and Ni in sediments showed that the methods based on sediment quality guidelines could judge the ecological risk more intuitively than the methods based on background value (PN, PLI, RI). The significant correlations between ecological risks and benthos density and biomass revealed the negative impact of trace metals at high concentrations on macrobenthic survival in sediments. Graphical abstract: Unlabelled Image Highlights: Trace metals were correlated with benthos by Ecological risk assessments. The increasing ecological risk will reduce benthic biodensity and biomass. Methods based on background value and SQG were used to evaluate the ecological risk. Mostly trace metals had higher concentrations in estuary than in other regions.